A Phenotypic High Throughput Screening Assay for the Identification of Pharmacoperones for the Gonadotropin Releasing Hormone Receptor - Conn, P. Michael (Mary Ann Liebert, Inc., 2014)
We describe a phenotypic high throughput screening (HTS) calcium flux assay designed to identify pharmacoperones for the gonadotropin releasing hormone receptor (GnRHR). Pharmacoperones are target-specific, small molecules that diffuse into cells, rescue misfolded protein mutants, and restore them to function. Rescue is based on correcting the trafficking of mutants that would otherwise be retained in the endoplasmic reticulum and unable to function correctly. This approach identifies drugs with a significant degree of novelty, relying on cellular mechanisms that are not currently exploited. Development of such assays is important, since the extensive use of agonist/antagonist screens alone means that useful chemical structures may be present in existing libraries but have not been previously identified using existing methods. Our assay utilizes cell lines stably expressing a GnRHR mutant under the control of a tetracycline (OFF) transactivator. This allows us to quantitate the level of functional and properly trafficked G protein coupled receptors present in each test well. Furthermore, since we are able to turn receptor expression on and off, we can rapidly eliminate the majority of false positives from our screening results. Our data show that this approach is likely to be successful in identifying hits from large chemical libraries.